Pelatihan Manajemen Referensi Mendeley bagi Mahasiswa Jurusan Pendidikan Teknik Elektro, Fakultas Teknik, Universitas Negeri Makassar - Haripuddin; Al Imran; Dessy Ana Laila Sari; Zulhajji; Muliaty Yantahin (Jurusan Teknik Informatika dan Komputer, 2023)
The focus of this program is Mendeley Reference Management Training for Electrical Engineering Education Students at FT UNM in Makassar City. The main challenge in putting this community service project into practice is figuring out how to improve the academic standards of students at Makassar State University's Faculty of Engineering, particularly in the Department of Electrical Engineering Education, by learning about and compiling a bibliography to support final assignment activities. According to the 2019 Final project Guidelines for the Faculty of Engineering, a bibliography should follow the guidelines provided and include information about all sources utilized in the research report and final project. Training is required to enhance students' abilities in reference management because the majority of students create bibliographies manually, which leads to a variety of issues, including inefficient writing of the bibliography. In order to create a good and appropriate bibliography or reference list that complies with the guidelines provided in the UNM FT Student Final Assignment Guidelines, this service activity aims to provide an understanding of the Mendeley application and how to use it.